CHAIR - Hadjimitsis, Diofantos G. (My University, 2026)
In the context ofWorldGeographicInformationSystemsDay,on16thofNovember2022,theERATOSTHENESCentreofExcellenceandtheCyprusUniversityofTechnologyorganizedaconferencededicatedtoGeographicInformationSystemsetitled"GISDay2022:ServicesandApplicationsofGeographicInformationSystemsinthePublicandPrivateSectorsofCyprus".TheconferencefocusedonthesignificanceofGeographicalInformationSystemsandtheirdiverseapplicationsinboththepublicandprivatesectorofCyprus.